2023
DOI: 10.1021/acs.chemmater.2c03568
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Growth of Hexagonal Boron Nitride on High-Aspect-Ratio Silicon-Based Nanotrenches

Abstract: We successfully accomplished the conformal growth of sp2-hybridized few-layer h-BN over an array of Si-based nanotrenches with a 45 nm pitch and an aspect ratio of ∼7:1 by using the pulsed-mode metal–organic chemical vapor deposition (MOCVD) method. Surface-sensitive X-ray absorption fine structure spectroscopy and density functional theory calculations revealed that the B–O bonds formed on the noncatalytic SiO2 surface act as nucleation sites for the subsequential formation of mixed sp2- and sp3-hybridized BO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It has a wide bandgap (4-6 eV), resulting in an insulating property. Like the above materials, h-BN has unique mechanical, electrical, [99] and thermal properties. [100] It has a high thermal conductance and can be effective for heat dissipation, [44,101] and so h-BN has been used as a protective layer to minimize material damage.…”
Section: D Materialsmentioning
confidence: 99%
“…It has a wide bandgap (4-6 eV), resulting in an insulating property. Like the above materials, h-BN has unique mechanical, electrical, [99] and thermal properties. [100] It has a high thermal conductance and can be effective for heat dissipation, [44,101] and so h-BN has been used as a protective layer to minimize material damage.…”
Section: D Materialsmentioning
confidence: 99%
“…However, the heterostructure of h-BN thin and catalytic substrates cannot satisfy the needs of various novel device integration. Combining the film with the target substrate by direct growth or transfer, such as GaN 9 , SiO 2 10 , diamond 11 , etc., is more conducive to exploring the performance potential of more new optical and power electronic devices. Among them, the h-BN/diamond heterostructure interfacial coupling electronic properties have attracted a lot of research.…”
Section: Introductionmentioning
confidence: 99%
“…As Khan et al reported, the growth of graphene on silicon (Si) substrates can lead to unwanted chemical bonding between Si and carbon (C) at 900 °C . Similarly, Kim et al demonstrated that boron (B) – oxygen (O) bonds could form during the growth of hexagonal-boron nitrite (h-BN) on silicon dioxide (SiO 2 ) substrates . All these unrelated bonds to 2D film formation can significantly impact the quality and performance of electronic and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Similarly, Kim et al demonstrated that boron (B) – oxygen (O) bonds could form during the growth of hexagonal-boron nitrite (h-BN) on silicon dioxide (SiO 2 ) substrates. 37 All these unrelated bonds to 2D film formation can significantly impact the quality and performance of electronic and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%